PENERAPAN MANAJEMEN RISIKO PADA PT ASDP (ANGKUTAN SUNGAI DANAU DAN PENYEBERANGAN) INDONESIA FERRY - Muhamad Rizki Fernanda (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
This study applies risk management to PT ASDP Indonesia Ferry to deal with the risks of river, lake and ferry transportation operations in Indonesia. Through a qualitative approach and case studies in companies, this study analyzes the adopted risk management practices. PT ASDP Indonesia Ferry has identified, evaluated and handled risks with structured steps and an integrated management framework. Management involvement, high risk awareness, effective communication and training, cooperation with related parties, strict operational guidelines, as well as prevention and recovery measures are key success factors. The implementation of effective risk management is important for operational safety and sustainability in the marine transportation industry.